Imprints of Rodinia break-up and earlier supercontinental assembly revealed in interior East Antartica - ARMADILLO, EGIDIO; BOZZO, EMANUELE; Ferraccioli F.; Jordan T. A.; Young D. A.; Blankenship D.; Anderson L.; Siegert M. J. (2011)
East Antarctica is often regarded as a keystone within the Rodinia supercontinent. However, both its position within Rodinia and the extent of Neoproterozoic rifting related to its break-up remain uncertain . Here we present recent aeromagnetic and airborne gravity datasets combined with satellite magnetic and gravity data to unveil the crustal architecture of the Neoproterozoic rifted margin of the East Antarctic shield in the Wilkes Subglacial Basin and Transantarctic Mountains region. We interpret a 1,900 km-long linear magnetic low along the edge of the composite (Proterozoic-Archean) Mawson continent as delineating a major Neoproterozoic rift system, connected to the Adelaide Rift Complex and other coeval rift zones in Australia. Our new magnetic anomaly compilation indicates that Neoproterozoic rocks exposed in the Central Transantarctic Mountains belong to the eastern branch of the rift system, which lies further outboard compared to the western rifts. A residual Bouguer gravity high extends for 1,000 km along the margin of the western rifts. By analogy with the edge of the Curnamona craton and Mt Isa province in Australia, we propose that the anomaly images an older Paleoproterozoic suture zone, which in turn controlled the location of Neoproterozoic rifting. Neoproterozoic rifting in East Antarctica appears to have been largely amagmatic compared to Australia, Laurentia, or China, where mantle plume-related giant dyke swarms and large igneous provinces accompanied early extension within Rodinia.